Studi Perbandingan Hukum Perseroan Perorangan di Indonesia dan India - Arum Tarina (Direktorat Penelitian dan Pengabdian (DPPM) Universitas Pelita Bangsa, 2023)
The Job Creation Law which resulted from the economic and legal reform came into force on November 2nd, 2020. It is the milestone of recognition of the legal state of a single-member company in law for the first time in Indonesia. While in India adopts and recognizes the legal status of One Person Company through The Companies Act, of 2013. By using the normative juridical method, this article discusses and explores the peculiarity and similarities between the legal system of One Person Company in Indonesia and India by analyzing and comparing some key provisions in each legal system, which both adhere to a mixed legal system, thus to shed light on the advantages and drawbacks of the current legal system, so as to inspire lawmakers in the future. From the results of this study, it can be concluded that in Indonesia the regulations governing One Person Company is still not detailed so as to provide space for multiple interpretations both for the government as the organizer of the establishment, amendment, and dissolution, as well as for the business actors themselves who will make One Person Company their business vehicle. Undang-Undang Cipta Kerja yang merupakan hasil reformasi ekonomi dan hukum mulai berlaku pada tanggal 2 November 2020. Ini merupakan tonggak pengakuan status hukum Perseroan Perorangan untuk pertama kalinya di Indonesia. Sementara di India mengadopsi dan mengakui status hukum One Person Company melalui The Companies Act, 2013. Dengan menggunakan metode yuridis normatif, artikel ini membahas dan mengeksplorasi kekhasan dan persamaan antara sistem hukum Perseroan Perorangan di Indonesia dan India dengan menganalisis dan membandingkan beberapa ketentuan utama di masing-masing sistem hukum, yang mana sama-sama menganut sistem hukum campuran, sehingga dapat menjelaskan kelebihan dan kekurangan dari sistem hukum saat ini, sehingga dapat menginspirasi pembuat undang-undang di masa depan. Dari hasil kajian ini dapat disimpulkan bahwa di Indonesia peraturan yang mengatur Perseroan Perorangan masih belum detil sehingga memberikan ruang multi interpretasi baik bagi pemerintah sebagai penyelenggara pendirian, perubahan, dan pembubaran, serta bagi pelaku usaha itu sendiri yang akan menjadikan Perseroan Perorangan sebagai kendaraan usahanya.